Patient Perceptions of Open, Laparoscopic, and Robotic Gynecological Surgeries. (20th October 2016) - Irani, Mohamad; Prabakar, Cheruba; Nematian, Sepide; Julka, Nitasha; Bhatt, Devika; Bral, Pedram
Abstract : Objective . To investigate patient knowledge and attitudes toward surgical approaches in gynecology. Design . An anonymous Institutional Review Board (IRB) approved questionnaire survey. Patients/Setting . A total of 219 women seeking obstetrical and gynecological care in two offices affiliated with an academic medical center. Results . Thirty-four percent of the participants did not understand the difference between open and laparoscopic surgeries. 56% of the participants knew that laparoscopy is a better surgical approach for patients than open abdominal surgeries, while 37% thought that laparoscopy requires the surgeon to have a higher technical skill. 46% of the participants do not understand the difference between laparoscopic and robotic procedures. 67.5% of the participants did not know that the surgeon moves the robot's arms to perform the surgery. Higher educational level and/or history of previous abdominal surgeries were associated with the highest rates of answering all the questions correctly (p < 0.05 ), after controlling for age and race. Conclusions. A substantial percentage of patients do not understand the difference between various surgical approaches. Health care providers should not assume that their patients have an adequate understanding of their surgical options and accordingly should educate them about those options so they can make truly informed decisions.